Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 41517 species occurrences available in GBIF matching the query: { "or" : [ "TaxonKey is Erythranthe (L.) G.L.Nesom", "TaxonKey is Mimulus L." ] } The dataset includes 41517 records from 274 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0004735-160526112335914/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences